METODE PENAFSIRAN AL-QURAN (TINJAUAN PANJANG PENDEK PENAFSIRAN, MODEL, KECENDERUNGAN MAZHAB, DAN CORAK PENAFSIRAN) - Novita, Ida; Rahman, Pathur (Mumtaz: Jurnal Studi Al-Quran dan Keislaman, 2023)
The aim of this research is to provide an explanation of: methods of interpreting the Koran. This research takes a qualitative study, while the type is library research. A descriptive-analytic approach is used in the study to completely describe the method of interpreting the Koran. The research findings show: that the method of interpreting the Al-Quran is a treasure of intellectual property in Islam itself. How could the Al-Quran, which is the greatest holy book revealed by Allah, contain various kinds of information about various sciences? Differences in ways and methods of understanding the Koran; First, in terms of the length and shortness of the interpretation, it produces a book of interpretation; A concise Tafsir of Jalalain and a complete Tafsir of Ibn Kathir. Second, viewed from the perspective of the interpretive model; Ijmali, Tahlili, Muqarin and Maudhu'i. Third, viewed from the point of view of school tendencies; Sunni, Shia, Muktazilah interpretations. Fourth, viewed from the perspective of interpretive style; Sufi, Lughawi, Fiqh, Falsafi, Adabi Ijtima'i, Ilmi and so on